PELATIHAN USAHA MINUMAN “KEKINIAN” UNTUK MENINGKATKAN JIWA KEWIRAUSAHAAN SANTRI PPSQ ASY-SYADZILI - Fathimatus Zahro Fazda Oktavia; Widi Dwi Ernawati; Dyah Metha Nur Fitriasih; Rika Wijayanti; Rosy Aprieza Puspita Zandra (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2021)
PPSQ Asy-Syadzili as one of the big boarding schools with a total of more than 1,000 students has extraordinary resources if used properly. So far, many resources have not been utilized optimally or are still managed by outsiders. Therefore, this service activity aims to help students take advantage of the internal and external resources and market share of the cottage and make it a place for direct learning how to be a polite and successful entrepreneurship. The concrete steps to be taken are to encourage students to have an entrepreneurial spirit. The business idea taken is a food and beverage business which is the basic needs of the students themselves. Because the activity was carried out during the pandemic, the training was carried out online by uploading tutorial videos on YouTube. The evaluation results after the training showed that participants had a high level of satisfaction, great benefits and the ability of participants to continue the results of the training in starting a business and teaching these skills to other residents. Participants give suggestions so that they can get other training in the future.